2015
DOI: 10.3758/s13420-015-0189-7
|View full text |Cite
|
Sign up to set email alerts
|

Rats’ midsession reversal performance: the nature of the response

Abstract: The midsession reversal task involves a simple simultaneous discrimination that predictably reverses midway through a session. Under various conditions, pigeons generally both anticipate the reversal and perseverate once it has occurred, whereas rats tend to make very few of either kind of error. In the present research, we investigated the hypothesis that the difference in performance between rats and pigeons is related to the nature of the responses made. We hypothesized that rats could have been better at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Although several newer studies have illuminated how changes in task demands can modulate the degree of this temporal control (Daniel et al, 2015; McMillan et al, 2014; McMillan & Roberts, 2012; McMillan et al, 2016; Rayburn-Reeves, Laude, et al, 2013; Rayburn-Reeves et al, under review), it is unclear why time has such a powerful influence on this species. Humans, and perhaps all mammals, appear to be far less influenced by time and more likely to attend to recent outcomes in guiding their switching behavior (Rayburn-Reeves et al, 2011; Rayburn–Reeves, Stagner, et al, 2013; A. P. Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several newer studies have illuminated how changes in task demands can modulate the degree of this temporal control (Daniel et al, 2015; McMillan et al, 2014; McMillan & Roberts, 2012; McMillan et al, 2016; Rayburn-Reeves, Laude, et al, 2013; Rayburn-Reeves et al, under review), it is unclear why time has such a powerful influence on this species. Humans, and perhaps all mammals, appear to be far less influenced by time and more likely to attend to recent outcomes in guiding their switching behavior (Rayburn-Reeves et al, 2011; Rayburn–Reeves, Stagner, et al, 2013; A. P. Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to reduce the relevancy and predictability of the timing cue by randomly varying across sessions the trial at which the discrimination reversal occurs (McMillan, Kirk, & Roberts, 2014; McMillan, Sturdy, Pisklak, & Spetch, 2016; Rayburn-Reeves, Laude, & Zentall, 2013; Rayburn-Reeves et al, 2011; Rayburn-Reeves & Zentall, 2013; A. P. Smith, Pattison, & Zentall, 2016).…”
Section: Control Of Switching Behavior By Reinforcement Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamentally, pigeons' responding across these sessions appears to be probabilistic rather than categorical, despite that the reversal itself is from 100% to 0% probability of reward (or vice versa). Research has soundly demonstrated the robustness of the midsession reversal timing errors even with variable, difficultto-predict reversal points (Rayburn-Reeves, Laude, & Zentall, 2013;Smith, Pattison, & Zentall, 2016). Even when actual switch points vary wildly across sessions, pigeons appear to form molar aggregate computations to anticipate the switch, and make only modest corrections based on a molecular "follow the reward" rule (Rayburn-Reeves, Laude, et al, 2013).…”
Section: Volume 12 2017mentioning
confidence: 99%
“…There has been a resurgence in interest in reversal learning, manifest in a raft of recent studies of “midsession reversal” (McMillan et al 2014; Rayburn-Reeves, et al 2011; Smith et al 2016; Stagner et al 2013). Generally, these studies find that pigeons make many anticipatory and perseverative errors when a reversal predictably occurs in the middle of a testing session.…”
Section: Discussionmentioning
confidence: 99%